2015
DOI: 10.1016/j.bpj.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Angle of Inclination of Tank-Treading Red Cells: Dependence on Shear Rate and Suspending Medium

Abstract: Red cells suspended in solutions much more viscous than blood plasma assume an almost steady-state orientation when sheared above a threshold value of shear rate. This orientation is a consequence of the motion of the membrane around the red cell called tank-treading. Observed along the undisturbed vorticity of the shear flow, tank-treading red cells appear as slender bodies. Their orientation can be quantified as an angle of inclination (θ) of the major axis with respect to the undisturbed flow direction. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
(65 reference statements)
2
11
0
Order By: Relevance
“…Typically, an RBC exposed to a shear flow may elongate and align itself at a constant angle with respect to the flow. We have investigated the angle inclination and in Reference we confirmed that our model corresponds to the experimental measurements of the inclination angle reported in Reference .…”
Section: Validating Dynamic Behavior—rotation Frequency In Shear Flowsupporting
confidence: 87%
See 2 more Smart Citations
“…Typically, an RBC exposed to a shear flow may elongate and align itself at a constant angle with respect to the flow. We have investigated the angle inclination and in Reference we confirmed that our model corresponds to the experimental measurements of the inclination angle reported in Reference .…”
Section: Validating Dynamic Behavior—rotation Frequency In Shear Flowsupporting
confidence: 87%
“…In References and , the blood samples were obtained from healthy blood bank volunteers. Chilling, centrifuge, and buffered salt solutions were used to obtain hematocrit of approximately 50%.…”
Section: Validating Dynamic Behavior—rotation Frequency In Shear Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Under certain flow conditions, a red blood cell in shear flow may tumble or exhibit a tank-treading motion of the membrane, depending on the shear rate [ 36 ]. We have investigated the inclination angle in [ 39 ] and confirmed that our model corresponds to the experimental measurements of the inclination angle reported in [ 40 ]. Further, in [ 34 ] we performed computational experiments of tank-treading frequency also reproducing the experimental results and thus validating the model.…”
Section: Design and Implementationsupporting
confidence: 83%
“…The RBCs in shear flow have been observed to exhibit two primary types of dynamics: tank treading (TT) motion and tumbling (TB) motion, depending on cell geometry (S/V ratio), cell elasticity (capillary number Ca µ = η oγ R 0 /µ where R 0 is the radius of a sphere with the same volume as an RBC), and fluid properties such as viscosity ratio (λ = η i /η o where η i and η o are the cytoplasm and suspending fluid viscosities) (25,(67)(68)(69)(70). At low shear rateγ, the resistance to shear causes RBCs to tumble.…”
Section: Dynamic Behavior Of Individual T2dm Rbc In Shear Flowmentioning
confidence: 99%